A QUALITATIVE STUDY OF EMPLOYEES’ WORK-LIFE BALANCE AND ORGANIZATIONAL COMMITMENT AT PT BANK MANDIRI (PERSERO) TBK MANADO - Sabijono, Kahana .; Saerang, David P.E; Tumewu, Ferdinand . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Knowing the importance of the existence of their employees, Bank Mandiri is concerned about their employees’ work-life balance and organizational commitment. This research is conducted with the purpose of knowing the work-life balance and organizational commitment at Bank Mandiri Manado. This research is a qualitative research that utilize data gathered from semi-structured interviews with 16 informants from Bank Mandiri Manado. The informants are selected by using purposive sampling. From the result of interview analysis, it is found that 12 out of 16  informants are having a healthy work-life balance in terms of involvement balance, and all of the informants are committed to Bank Mandiri in terms of continuance commitment. In order to help the employees balancing their work and life, Bank Mandiri should consider to provide on-site child care in Bank Mandiri Manado, and also should consider to implement culture-change strategy such as training for the managers to help the employees to manage work-life conflicts. To increase the employees’ organizational commitment, Bank Mandiri should consider to increase the salary and improve the benefits offered to the employees.Keywords: work-life balance, organizational commitment, bank mandiri, qualitative study.